Antioxidant Alternatives in the Treatment of Amyotrophic Lateral Sclerosis: A Comprehensive Review - Carrera-Juliá, Sandra; Moreno, Mari Luz; Barrios, Carlos; de la Rubia Ortí, Jose Enrique; Drehmer, Eraci (Frontiers in Physiology, 2020)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that produces a selective loss of the motor neurons of the spinal cord, brain stem and motor cortex. Oxidative stress (OS) associated with mitochondrial dysfunction and the deterioration of the electron transport chain has been shown to be a factor that contributes to neurodegeneration and plays a potential role in the pathogenesis of ALS. The regions of the central nervous system affected have high levels of reactive oxygen species (ROS) and reduced antioxidant defences. Scientific studies propose treatment with antioxidants to combat the characteristic OS and the regeneration of nicotinamide adenine dinucleotide (NAD+) levels by the use of precursors. This review examines the possible roles of nicotinamide riboside and pterostilbene as therapeutic strategies in ALS.